THE THREAT OF ECONOMIC RECESSION AND ITS IMPACT ON GLOBAL TERRORISM - Anshori, Ahmad Bahrul; napang, marthen; Nurhasanah, Siti (Journal of Terrorism Studies, 2020)
World economic growth in 2020 is predicted to experience a recession as a result of the Covid-19 pandemic. One of the effects of the economic recession is the threat to global security stability, especially terrorism will flourish. This research aims to analyze the impact of the threat of the economic recession of 2020 on the development of a global terrorism network. The method used in this research is an explorative descriptive qualitative method using data collection techniques namely observation and literature study. The results of this study conclude that the potential for the economic recession of 2020 which threatens many countries in the world can be a determinant factor in strengthening the global terrorism network. For the Indonesian context, the Jamaah Islamiah (JI) group, which since the emergence of ISIS chose to become a sleeping cell, with the collapse of ISIS in mid-2019 and supported by economic recession conditions, will make JI freer to rebuild its organization. To anticipate the condition of the strengthening of the global terrorism network, the Indonesian government can make several efforts, including strengthening the cooperation of the government and the community to close the gaps of the possibility of terrorist groups opening a jihad front in Indonesia, because, with the death of al-Baghdadi, ISIS groups will almost certainly leave from the land of Syria and Iraq, and need another earth to serve as a new foothold for jihad. The government must also realize justice because terrorists often make the issue of injustice a medium for mobilizing global and regional terrorism networks. Also, the Indonesian government together with leaders and international organizations, including the United Nations (UN), should enhance intelligence cooperation by also involving the public and private sector.